PENDIDIKAN KARAKTER BERBASIS BRAIN BASED EDUCATION - Abu Hasan Agus R. (Nurul Jadid University, 2016)
Learning is a relatively permanent change in behavior as a result of ex- perience (intentional) and applied to other knowledge and able mengko- munikasikann to others. For this purpose, we need a lesson organized and interconnected with each other. New paradigm known as brain-compatible learning or brain-based education that is based on the brain’s ability to appear with stunning implications for teachers and learners around the world. Based on disciplines in neuroscience, biology and psychology, our understanding of the relationship between education and brain now leads us to the role of emotions, patterns, meanings, environment, music, move- ment, and enrichment. At the level of the concept of early childhood edu- cation, coaching and development of children associated with the forma- tion of human character completely. ECD is essential for the survival of the nation, it is important and needs to be taken seriously by the govern- ment. ECD as a human resource development strategy should be seen as a central point of considering the establishment of national character and reliability of human resources determined how planting since early child- hood, the importance of education in this period, so often referred to as the golden ages